A proactive approach to supply chain risk management: Shifting orders among suppliers to mitigate the supply side risks. Issue 1 (January 2017) - Kırılmaz, Oguzhan; Erol, Serpil
Abstract: Globalization, e-trade, advanced technologies and emerging production techniques have increased supply chains' efficiency and added value. However, despite numerous advantages, these factors make supply chains more fragile and vulnerable to risks. For this reason, companies that perform supply chain risk management gain competitive advantage. In the past, supply chain managers mainly focused on reducing costs; but recently, they have begun to give importance to supply chain continuity and resiliency which have significant impacts on costs as well. Hence, conventional reactive planning has given way to proactive planning in supply chain risk management. In this study, the supply chain risk management process is investigated and a procedure is proposed in the risk mitigation phase. In the first stage of the proposed procedure, an initial procurement plan is obtained via a linear programming model, considering the cost criterion as the first priority. In the second stage, this plan is revised by including the risk criterion into the planning as the second priority. The aim of this procedure that enables proactive planning is to reduce the supply side risks. The model is tested with a hypothetical data set and the cost analysis is performed to evaluate the performance of the procedure. Finally, the whole supply chain risk management process including the proposed procedure is applied to an international automotive company. Highlights: A unique risk mitigation procedure is proposed to reduce the supply side risks. Linear programming is used in risk mitigation. Not only cost but risk criterion is included quantitatively in procurement planning. Risk impact can be identified in terms of physical loss, social loss, time loss etc.